Immobilisation of hydroxyapatite-collagen on polydopamine grafted stainless steel 316L: Coating adhesion and in vitro cells evaluation - Tapsir, Zafirah; Jamaludin, Farah Hidayah; Pingguan-Murphy, Belinda; Saidin, Syafiqah (SAGE Publications, 2018)
The utilisation of hydroxyapatite and collagen as bioactive coating materials could enhance cells attachment, proliferation and osseointegration. However, most methods to form crystal hydroxyapatite coating do not allow the incorporation of polymer/organic compound due to production phase of high sintering temperature. In this study, a polydopamine film was used as an intermediate layer to immobilise hydroxyapatite-collagen without the introduction of high sintering temperature. The surface roughness, coating adhesion, bioactivity and osteoblast attachment on the hydroxyapatite-collagen coating were assessed as these properties remains unknown on the polydopamine grafted film. The coating was developed by grafting stainless steel 316L disks with a polydopamine film. Collagen type I fibres were then immobilised on the grafted film, followed by the biomineralisation of hydroxyapatite. The surface roughness and coating adhesion analyses were later performed by using AFM instrument. An Alamar Blue assay was used to determine the cytotoxicity of the coating, while an alkaline phosphatase activity test was conducted to evaluate the osteogenic differentiation of human fetal osteoblasts on the coating. Finally, the morphology of cells attachment on the coating was visualised under FESEM. The highest RMS roughness and coating adhesion were observed on the hydroxyapatite-collagen coating (hydroxyapatite-coll-dopa). The hydroxyapatite-coll-dopa coating was non-toxic to the osteoblast cells with greater cells proliferation, greater level of alkaline phosphate production and more cells attachment. These results indicate that the immobilisation of hydroxyapatite and collagen using an intermediate polydopamine is identical to enhance coating adhesion, osteoblast cells attachment, proliferation and differentiation, and thus could be implemented as a coating material on orthopaedic and dental implants.